PENGARUH KECERDASAN EMOSIONAL, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA TUTOR DI KABUPATEN GOWA - Siti Nursyamsi; Andi Mappatompo (COMPETITIVENESS, 2018)
This study aims to determine the effect of emotional intelligence on the performance of PAUD SPAS tutors in Sombaopu District, Gowa Regency. This research was conducted in Sombaopu Subdistrict, Gowa Regency with an implementation time of 2 months, namely January to February 2018 with a sample of 42 people. The type of data used in this research is quantitative data.The Emotional Intelligence variable (X1) has a positive and significant effect on the performance of PAUD SPAS tutors in Sombaopu District, Gowa Regency. The results of the hypothesis test show that the t significance value of the emotional intelligence variable is smaller than 0.05 so that Ho is rejected and Ha is accepted, which means that the hypothesis which states "Emotional Intelligence has a positive and significant effect on the performance of PAUD SPAS tutors in Sombaopu District, Gowa Regency" is proven. Work Motivation Variable (X2) has a positive and significant effect on the performance of PAUD SPAS tutors in Sombaopu District, Gowa Regency. The results of the hypothesis test show that the t significance value of the work motivation variable is less than 0.05, so that Ho is rejected and Ha is accepted, meaning that the hypothesis which states "Work motivation has a positive and significant effect on the performance of PAUD SPAS tutors in Sombaopu District, Gowa Regency" is proven. Work Environment Variable (X3) has a positive effect although not significant on the performance of PAUD SPAS tutors in Sombaopu District, Gowa Regency. The results of the hypothesis test show that the t significance value of the work environment variable is greater than 0.05, so that Ho is accepted and Ha is rejected, which means that the hypothesis which states "Work Environment has a positive and significant effect on the performance of PAUD SPAS tutors in Sombaopu District, Gowa Regency" is not proven. . Of the three variables analyzed, namely emotional intelligence (X1), motivation (X2) and work environment (X3), it turns out that the one that has the greatest influence or highest contribution to performance is the emotional intelligence variable (X1) with a standardized coefficients beta value of 0.455 and variable The work environment (X3) with the smallest influence or smallest contribution is the standardized coefficients beta value of 0.170. Keywords: Emotional Intelligence, Motivation and Work Environment